Assessing the Impact of Dental Implant Length on Early Failure Rates: A Retrospective Analysis - Bhuvaneshwari Karthikeyan; K Hanumantha Kumar; K. Sadananda; Inderjit Murugendrappa Gowdar; Shital J. Sonune; Doaa Abdelaziz A. Helal (Wolters Kluwer Medknow Publications, 2024)
Introduction: The selection criteria of implant is very critical. Implant length determines the mechanics of osseointegration. Objective: To investigate the influence of dental implant length on early failure rates, osseointegration success, peri-implant bone loss, and patient-reported outcomes. Materials and Methods: A retrospective analysis was conducted involving 124 participants who underwent dental implant placement. Implant lengths were categorized as short (n = 54), standard (n = 35), or long (n = 35) based on standard industry classifications. Baseline characteristics, implant lengths, and early failure rates within the first six months post-implantation were extracted from clinical records. Results: Preliminary analysis revealed variations in early failure rates among different implant length categories. Short implants demonstrated a distinct pattern of complications compared to standard and long implants. Early failure rates were 8% for short implants, 4% for standard implants, and 2% for long implants (P = 0.04). Osseointegration success rates were 90%, 95%, and 98% for short, standard, and long implants, respectively. Peri-implant bone loss was 1.5 mm, 1.0 mm, and 0.8 mm for short, standard, and long implants, respectively (P = 0.02). Patient-reported outcomes indicated higher satisfaction levels in the long implant group (P = 0.03). Conclusion: The study highlights the importance of considering implant length in clinical decision-making and suggests potential associations with osseointegration success, peri-implant bone loss, and patient satisfaction.